Prevalence and methodologies for detection, characterization and subtyping of Listeria monocytogenes and L. ivanovii in foods and environmental sources - Jin-Qiang Chen; Patrick Regan; Pongpan Laksanalamai; Stephanie Healey; Zonglin Hu (Food Science and Human Wellness)
Listeria monocytogenes, one of the most important foodborne pathogens, can cause listeriosis, a lethal disease for humans. L. ivanovii, which is closely related to L. monocytogenes, is also widely distributed in nature and infects mainly warm-blooded ruminants, causing economic loss. Thus, there are high priority needs for methodologies for rapid, specific, cost-effective and accurate detection, characterization and subtyping of L. monocytogenes and L. ivanovii in foods and environmental sources. In this review, we (A) described L. monocytogenes and L. ivanovii, world-wide incidence of listeriosis, and prevalence of various L. monocytogenes strains in food and environmental sources; (B) comprehensively reviewed different types of traditional and newly developed methodologies, including culture-based, antigen/antibody-based, LOOP-mediated isothermal amplification, matrix-assisted laser desorption ionization-time of flight-mass spectrometry, DNA microarray, and genomic sequencing for detection and characterization of L. monocytogenes in foods and environmental sources; (C) comprehensively summarized different subtyping methodologies, including pulsed-field gel electrophoresis, multi-locus sequence typing, ribotyping, and phage-typing, and whole genomic sequencing etc. for subtyping of L. monocytogenes strains from food and environmental sources; and (D) described the applications of these methodologies in detection and subtyping of L. monocytogenes in foods and food processing facilities.